CODE MIXING AND CODE-SWITCHING FOUND IN CINTA LAURA KIEHL'S SELECTED SONGS - Pasaribu, Cintana Marito; Dianti, Hilmina Rahma; Iffah, Ida Farhatul; Putri, Intan Cahyani; Sarrohmahniyati, Sarrohmahniyati; Nargis, Nargis (Media Inovasi Pendidikan dan Publikasi, 2025)
This research analyzes the use of code-mixing and code-switching in selected song lyrics by Cinta Laura Kiehl. The research aims to identify the types of code-mixing and code-switching that appear in five selected songs: